AN ANALYSIS OF ENDOPHORIC REFERENCE COHESION DEVICES IN MARK ZUCKERBERG BIOGRAPHY - Melani Siti Khalifah; Juan Carlina Wibowo; Cynantia Rachmijati (IKIP Siliwangi, 2019)
The aim of the research is to find out endophoric references in Mark Zuckerberg biography and the relationship between discourse analysis and pragmatic. The research used descriptive qualitative research design. The data obtained from Mark Zuckerberg biography written by the biography website. The data are analyzed using Halliday & Hasan’s theory (1976) of reference cohesion reference is one of the cohesive devices. The result shows that endophoric reference exists in Mark Zuckerberg biography endophoric. Endophoric consist of two types, the first is anaphoric and the second is cataphoric. In this research there are five type cohesive devices that are usually used in texts like substitution, references, ellipsis, lexical cohesion, and conjunctions. In the research found that cataphoric is dominant than anaphoric because the subject is located in the beginning of the sentences. Cohesive devices not only focused on lexical cohesion, but also focused on ellipsis and substitution and reference.